Graphical ekphrasis in contemporary music - Metcalf, TMK (2021)
This thesis is, primarily, a treatise supporting a new approach to ekphrastic frameworks within contemporary music. Deriving from the Greek for ‘description’ [ἔκφρασις], ekphrasis traditionally relates to descriptions of art works as literary devices, with Keats’ Ode on a Grecian Urn (1819) being a well-known example. Through a re-evaluation and extension of Siglind Bruhn’s seminal work on ekphrasis within a musical context, I suggest that the construction of compositional grammars deriving from distinctly visual stimuli allows for a deeply embedded poetic and formal connection between the two media, which I deem a 'graphical ekphrasis'. To demonstrate this concept, three case studies are used which exhibit a variety of compositional methods and graphical sources. The first two studies adopt a largely work-centric focus, taking score analysis as the key interrogative method, supported by composer testimony or writings. The final case study explores the place of graphical ekphrasis in my own music, highlighting the potential of the rhetorical model and compositional method. Finally, an argument is proposed for the ways in which this concept may be developed, focusing on the construction of a composite framework for ‘transmedial’ aesthetics which can cut across both historical periodisation and disciplinary boundaries.